The Royalist war effort in Wales and the West Midlands, 1642-1646 - Hutton, R; Ronald Hutton (1980)
﻿ The essential object of the thesis is to examine the demands made upon differing royalist leaders during the Great Civil War, and the responses of those communities to them. By doing so, it is intended to provide answers to one of the great unanswered problems of the war, the question of whether the royalists lost because they were defeated in the field or because they forfeited the sympathy of the local people upon whose support they depended. The region chosen for study comprises twenty counties within Wales, the Marches and the West Midlands, the area in which the king first gathered an army and in which his supporters staged their last stand. The first section traces the delivery and impact of the royalist Commissions Of Array, the raising of the royal field army and the slow organisation of local communities for a prolonged war in the winter that followed. The second describes the completion of this process with the appointment of peers as regional generals. The third section is devoted to describing the machinery of royalist wartime government and the problems it faced. The fourth recounts how the noble generals came to be replaced by nore experienced soldiers, led by Prince Rupert. The fifth examines the challenge offered to these men in the winter of 1644-5 by a now war-weary local population, and the manner in which the military men overcame this challenge. The last section is devoted to showing how the destruction of the royal army at Naseby freed the local population to oppose any further demands by the royalist war machine and thereby destroy the machine itself.